Basic SolatFor Autism- A development guidance Mobile Apps (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Basic SolatFor Autism – An Islamic basic salat app that uses prayer psychotherapy and repeating learning to betterment in term of communication and social problems for autism kids. The apps targeted mild autism male kids aged 6 to 12. In the app there are learning part that focus on wudu’ and prayers, while gaming part that have quiz and puzzle which will have 3 level each mode. There are few kids’ app in the market that teach about Islamic prayer, but the app does not focus on the need of autism. Multimedia Mobile Content Development (MMCD) is used as the methodology to develop the learning apps. MMCD covers all the need in creating a learning apps for kids. The result from the alpha and beta testing shows that the app is useful and interesting and it is suitable for autism, as the app work like it should in alpha and 92.63% for beta test ing. However, there are a few improvements can be done in the future